Soleus H-reflex operant conditioning changes the H-reflex recruitment curve. - Thompson, Aiko K.; Xiang Yang Chen; Jonathan Wolpaw (Muscle & nerve, 2013)
INTRODUCTION: Operant conditioning can gradually change the human soleus H-reflex. The protocol conditions the reflex near M-wave threshold. In this study we examine its impact on the reflexes at other stimulus strengths. METHODS: H-reflex recruitment curves were obtained before and after a 24-session exposure to an up-conditioning (HRup) or a down-conditioning (HRdown) protocol and were compared. RESULTS: In both HRup and HRdown subjects, conditioning affected the entire H-reflex recruitment curve. In 5 of 6 HRup and 3 of 6 HRdown subjects, conditioning elevated (HRup) or depressed (HRdown), respectively, the entire curve. In the other HRup subject or the other 3 HRdown subjects, the curve was shifted to the left or to the right, respectively. CONCLUSIONS: H-reflex conditioning does not simply change the H-reflex to a stimulus of particular strength; it also changes the H-reflexes to stimuli of different strengths. Thus, it is likely to affect many actions in which this pathway participates.
Keywords: motor learning; plasticity; Rehabilitation; Spinal Cord

Acquisition of a simple motor skill: task-dependent adaptation plus long-term change in the human soleus H-reflex. - Thompson, Aiko K.; Xiang Yang Chen; Jonathan Wolpaw (The Journal of neuroscience : the official journal of the Society for Neuroscience, 2009)
Activity-dependent plasticity occurs throughout the CNS. However, investigations of skill acquisition usually focus on cortex. To expand the focus, we analyzed in humans the development of operantly conditioned H-reflex change, a simple motor skill that develops gradually and involves plasticity in both the brain and the spinal cord. Each person completed 6 baseline and 24 conditioning sessions over 10 weeks. In each conditioning session, the soleus H-reflex was measured while the subject was or was not asked to increase (HRup subjects) or decrease (HRdown subjects) it. When the subject was asked to change H-reflex size, immediate visual feedback indicated whether a size criterion had been satisfied. Over the 24 conditioning sessions, H-reflex size gradually increased in six of eight HRup subjects and decreased in eight of nine HRdown subjects, resulting in final sizes of 140 +/- 12 and 69 +/- 6% of baseline size, respectively. The final H-reflex change was the sum of within-session (i.e., task-dependent) adaptation and across-session (i.e., long-term) change. Task-dependent adaptation appeared within four to six sessions and persisted thereafter, averaging +13% in HRup subjects and -15% in HRdown subjects. In contrast, long-term change began after 10 sessions and increased gradually thereafter, reaching +27% in HRup subjects and -16% in HRdown subjects. Thus, the acquisition of H-reflex conditioning consists of two phenomena, task-dependent adaptation and long-term change, that together constitute the new motor skill. In combination with previous data, this new finding further elucidates the interaction of plasticity in brain and spinal cord that underlies the acquisition and maintenance of motor skills.
Keywords: H-Reflex; motor learning; motor skill; operant conditioning; plasticity; Spinal Cord

Modulation in spinal circuits and corticospinal connections following nerve stimulation and operant conditioning. - Thompson, Aiko K.; Stein, Richard B.; Xiang Yang Chen; Jonathan Wolpaw (Conference proceedings : ... Annual International Conference of the IEEE Engineering in Medicine and Biology Society. IEEE Engineering in Medicine and Biology Society. Conference, 2006)
Neural plasticity occurs throughout adult life. In healthy individuals, different spinal pathways are differently modulated during different daily activities. Drastic changes to nervous system activity and connections caused by injuries or diseases alter spinal reflexes, and this is often related to disturbed motor functions. In both health and disease, spinal reflexes are subject to substantial modifications. Plasticity in supraspinal descending connections is even more remarkable; corticospinal connectivity has been shown to be extremely plastic. In this session, we describe two approaches for possibly improving recovery after central nervous system (CNS) lesions. They are very different, but both involve repetitive nerve stimulation and CNS plasticity. The first approach is functional electrical stimulation (FES) of the common peroneal nerve, which has been used to treat foot drop in patients with CNS lesions. The second approach is operant conditioning of a spinal reflex. Spinal reflex operant conditioning studies in animal models have shown plastic changes in spinal cord neurons associated with this form of learning and improved locomotor function in incomplete spinal cord injured rats. Thus, reflex conditioning might be a robust approach to inducing plasticity at spinal and supraspinal levels. As a first step in establishing this approach and characterizing its effects in the human adult CNS, we are currently investigating the extent and time course of operant conditioning of the soleus H-reflex in healthy subjects. In results to date, all subjects (n=5) have changed reflex size in the correct direction to various degree (16-36%) over 2-3 months of conditioning, indicating possibility that H-reflex conditioning can occur in humans. At the same time, the substantial inter-subject variation in the time course and extent of conditioning suggest that additional data are needed to establish its principal features. We hope that studying modulation and modification o- f the CNS by different approaches will help us further understand the plasticity of the human adult nervous system.
Keywords: Spinal Cord